Mechanisms of reducing postoperative pain, nausea and vomiting: a systematic review of current techniques. Issue 3 (14th March 2012) - Rawlinson, Alex; Kitchingham, Nina; Hart, Colin; McMahon, Gregory; Ong, Seok Ling; Khanna, Achal
Abstract : Background: Multimodal recovery programmes decrease hospital stay. The objective of this systematic review was to assess how single-modality evidence-based care principles, regarding postoperative analgesia and postoperative nausea and vomiting (PONV) prophylaxis, combine to achieve this. Methods: A systematic review of randomised controlled trials was performed. Relevant trials compared postoperative epidural analgesia/parenteral opioid analgesia/paracetamol/non-steroidal anti-inflammatory drugs (NSAIDs) and postoperative antiemetics. The effect on recovery was evaluated in terms of length of hospital stay, pain intensity, duration of gastrointestinal dysfunction and incidence of PONV. Results: Twenty-three trials were included. Epidural anaesthesia failed to reduce length of stay or the incidence of PONV when compared to controls. Pain intensity and time to first bowel movement were reduced (p<0.05). Paracetamol did not reduce the incidence of PONV. NSAIDs reduced postoperative opioid consumption and the incidence of PONV (p<0.05). Dexamethasone and 5-HT3 antagonists reduced the incidence of PONV compared to controls. Conclusions: Epidural anaesthesia appears to not reduce length of hospital stay or incidence of PONV despite reducing pain intensity and ileus. NSAIDs are more effective than paracetamol in reducing postoperative opioid consumption and PONV, while dexamethasone and 5-HT3 antagonists are both effective in reducing PONV.